Morphological and physiological caste differences in Synoeca cyanea (Hymenoptera, Vespidae, Epiponini) according to the ontogenetic development of the colonies - Noda, Silvia Cristina Mari [UNESP]; Shima, Sulene Noriko [UNESP]; Noll, Fernando Barbosa (My University, 2003)
Morphological caste differences in different stages of the biological cycle in Synoeca cyanea were not distinct. Females presented a gradual sequence in ovarian development from filamentous ovarioles to well developed ones with the presence of intermediates, with shorter ovaries than queens, which can be present or not according to the stage of colonial development. Such data suggest that access to the reproductive status would only be possible in some intervals of colonial development.
Keywords: Epiponini; Hymenoptera; Invertebrata; Synoeca; Vespidae